University Students’ Awareness and Willingness to Intervene: Bystander Response to Peer Suicidal Risk in Kyrgyzstan - Salimova, Leila; Nurbaeva, Meerim K.; Agbo, Noah (Indonesian Social Work Consortium (ISWC), 2025)
While suicide is widely recognized as a serious concern, there is limited research on how young people perceive and respond to suicide risk among their peers. Our research aims to explore Kyrgyzstani university students' awareness and personal connections to suicide risk among peers, as well as their likelihood to intervene. We conducted a cross-sectional survey among 239 university students in Kyrgyzstan, employing an instrument based on the Bystander Intervention (BSI) Model. Responses were analyzed using descriptive statistics, visualizations, and thematic grouping of open-ended questions to identify trends and insights. Students show a strong awareness of the severity in Kyrgyzstan. While students view suicidal ideation as an emergency, they struggle to identify manipulative behaviors and specific signs. Students are generally willing to intervene but lack the knowledge and confidence for concrete actions. This study highlighted the critical role of personal experience, awareness, and skill development in shaping students' readiness to support peers at suicidal risk, emphasizing the need for targeted educational interventions to equip bystanders with effective knowledge and resources for proactive suicide prevention.